MARGIN ANALYSIS OF PORK TRADERS' MARKETING IN THE KAWANGKOAN TRADITIONAL MARKET, MINAHASA REGENCY - Oroh, Franky N.S; Lumenta, Ingriet D. R. (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2025)
The objectives of this study were (1) To determine the pork marketing channels that occur in the Kawangkoan Traditional Market, Kawangkoan District, Minahasa Regency, (2) To analyze marketing margins at each level of pork marketing institutions in the Kawangkoan Traditional Market, Kawangkoan District, Minahasa Regency and (3) To analyze farmer's share of pork marketing in the Kawangkoan Traditional Market, Kawangkoan District, Minahasa Regency. This study was conducted in August 2022 at the Kawangkoan Traditional Market, Kawangkoan District, Minahasa Regency. The data sources used in this study are primary data and secondary data. The sample of respondents in this study consisted of farmers (producers), collectors, retailers and end consumers. The sample of farmers (producers) and consumers was determined using the purposive sampling method. The sample of collectors and retailers was determined using the snowball sampling method. The data analysis model used in this study is descriptive analysis, marketing margin analysis and farmer's share. The results of the study indicate that there are 2 pork marketing channels in the Kawangkoan traditional market, Kawangkoan District, Minahasa Regency. Marketing margins in channels I and II are both Rp. 30,000/kg, however, due to the presence of different intermediary institutions, the profit sharing is different. Farmer's share in marketing channels I and II still appears to be quite efficient at 53.85%, meaning that for every Rp. 100 paid by consumers, farmers (producers) only receive around Rp. 53.85 and the remaining Rp. 46.15 is the share for other intermediary institutions (collectors and retailers), including profit margins and marketing costs